PELAKSANAAN PROSEDUR REKENING GIRO NASABAH PADA BANK SUMUT - Hesti Sitanggang; Irma Manik; Naomi Hutajulu; Tiur Sitanggang; Meliana Manurung; Christnova Hasugian; Hamonangan Siallagan (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research examines the implementation of customer checking account procedures at Bank Sumut with a focus on the efficiency of the account opening process, customer service, data security and protection, and technology adoption. Qualitative research methods, with a case study design, were used to gain an in-depth understanding of banking practices at Bank Sumut. The research results show that the procedure for opening a checking account is efficient, customer service is considered adequate, and the bank places security and data protection as a top priority. In addition, the adoption of technology, especially through digital banking applications, provides a convenient alternative for customers. However, the research also identifies future challenges and opportunities and provides recommendations for further development. These findings provide insight for Bank Sumut to improve services, maintain security, and face the dynamics of the banking industry.